2010
DOI: 10.1007/s12562-010-0295-6
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and characterization of Dmc1, a gene involved in gametogenesis, from the whiteleg shrimp Litopenaeus vannamei

Abstract: In order to gain a better understanding of the developmental processes of shrimp germ cells, the molecular cloning and characterization of a meiosis-related gene, Dmc1, was carried out using the whiteleg shrimp Litopenaeus vannamei. The cDNA of the L. vannamei Dmc1 homologue (LvDmc1) was 1,647 bp long and contained a 1,023-bp open reading frame corresponding to 341 amino acid residues. The deduced amino acid sequence contained motifs conserved in the RecA/Rad51 superfamily to which Dmc1 homologues belong and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
14
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 33 publications
2
14
1
Order By: Relevance
“…This expression pattern would suggest EsDmc1 could be expressed at earlier developmental stages before reproductive maturity in E. sinensis. Contrary to the results from L. vannamei, P. monodon Dmc1 did not show gonad-specific expression [14][15][16], indicating the complex roles of Dmc1 in crustaceans. Further investigations regarding crab Dmc1, particularly functional studies, are needed to determine the biological roles of this gene in crustaceans.…”
contrasting
confidence: 99%
See 4 more Smart Citations
“…This expression pattern would suggest EsDmc1 could be expressed at earlier developmental stages before reproductive maturity in E. sinensis. Contrary to the results from L. vannamei, P. monodon Dmc1 did not show gonad-specific expression [14][15][16], indicating the complex roles of Dmc1 in crustaceans. Further investigations regarding crab Dmc1, particularly functional studies, are needed to determine the biological roles of this gene in crustaceans.…”
contrasting
confidence: 99%
“…EsDmc1 displayed 87.3% identity with published Dmc1 of L. vannamei (LvDmc1), 86.5% with P. monodon (PmDmc1), 77.4% with Ixodes scapularis (IsDmc1), 75.9% with Anguilla japonica (AjDmc1) and 74.8% with Homo sapiens (HsDmc1). As reported in LvDmc1 [16], multiple alignments revealed that EsDmc1 contained motifs conserved in the RecA/Rad51 superfamily, including L1 and L2 loops, which are single-strand DNA binding motifs [25,26], and the Walker A and B motifs of the ATP binding site [26,27] (Figure 3). Moreover, the helix-hairpin-helix (HhH) motif, a double-strand DNA binding site that is commonly present in Rad51 and Dmc1, but not in RecA [26,28,29], was also detected in EsDmc1.…”
Section: Homologous and Phylogenetic Analysis Of Esdmc1supporting
confidence: 55%
See 3 more Smart Citations